An interactive feedback system for increasing hand antisepsis adherence in stationary intensive care. (March 2023) - Zwicker, P.; Meng, M.; Friesecke, S.; Stein, T.; Herzog, A.; Herzer, C.; Kammerlander, M.; Gebhardt, T.; Kugler, C.; Kramer, A.
Summary: Background: Pathogens causing infections are in many cases transmitted via the hands of personnel. Thus, hand antisepsis has strong epidemiological evidence of infection prevention. Depending on various factors, hand antisepsis adherence ranges between 9.1% and 85.2%. Aim: To evaluate a new transponder system that reminded medical staff to use an alcohol-based hand rub based on indication by giving real-time feedback, to detect hand antisepsis adherence. Methods: The monitoring system consisted of three components: a portable transponder detecting alcohol-based hand rub and able to give feedback; a beacon recognizing entries to and exits from the patient's surroundings; and a sensor placed at the hand-rub dispensers to count the number of hand rubs. With these components, the system provided feedback when hand antisepsis was not conducted although it was necessary according to moments 1, 4, and 5 of hand antisepsis. Adherence was measured in two use-cases with five phases, starting with the baseline measurement followed by intervention periods and phases without intervention to test the sustainability of the feedback. Findings: Using the monitoring system, hand antisepsis adherence was increased by up to 104.5% in comparison to the baseline measurement. When the intervention ceased, however, hand antisepsis adherence decreased to less than or equal to the baseline measurement. Conclusion: A short-term intervention alone is not sufficient to lead to a long-term change in hand antisepsis adherence. Rather, permanent feedback and/or the integration in a multi-modal intervention strategy are necessary.